How to Increase Trade in Southeast Europe by Applying Trade Facilitation Measures? - Makrevska disoska, Elena; Bjelic, Predrag; Kikerkova, Irena; Toshevska Trpchevska, Katerina (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
In this paper, we apply the 2021 edition of OECD Trade Facilitation Indicators (TFIs) in the gravity model to measure the importance of applying trade facilitation measures to increase intraregional trade among the 10 SEE countries: Albania, Bosnia & Herzegovina, Bulgaria, Croatia, Macedonia, Moldova, Montenegro, Romania, Serbia, and Slovenia. The purpose of the paper is to indicate area(s) where countries could undertake measures to facilitate trade and enhance the process of trade integration in the region of Southeast Europe. Although most of these countries trade among themselves on a preferential basis, many studies pointed out that there are still areas and barriers that hinder their mutual trade. The results of our study show that decreasing fees and charges, harmonization and decreasing the number of documents, automatizing the process of trading, and improving governance and impartiality of the Customs administration could positively influence trade among these countries. These results are additional confirmation of our previous studies in this area which firmly acknowledge the area where trade policy creators should pay due attention.
Keywords: SEE countries; OECD 2021 Trade Facilitation Indicators; gravity model; trade policy; trade facilitation